2019
DOI: 10.1021/acs.jpca.9b03813
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Investigations of the CH (X2Π) Radical Reaction with Cyclopentadiene

Abstract: The reaction of the ground state methylidyne radical (CH (X 2 Π)) with cyclopentadiene (C 5 H 6 ) is studied in a quasi-static reaction cell at pressures ranging from 2.7 to 9.7 Torr and temperatures ranging from 298 to 450 K. The CH radical is generated in the reaction cell by pulsed-laser photolysis (PLP) of gaseous bromoform at 266 nm, and its concentration monitored using laser-induced fluorescence (LIF) with an excitation wavelength of 430.8 nm. The reaction rate coefficient is measured to be 2.70(±1.34) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 88 publications
0
27
0
Order By: Relevance
“…The mechanism is depicted in Scheme 1, with the C atoms numbering and the relative energies of the stationary points in parenthesis (kJ mol À1 ). The names of the species participating in the mechanism are taken from the Caster work [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism is depicted in Scheme 1, with the C atoms numbering and the relative energies of the stationary points in parenthesis (kJ mol À1 ). The names of the species participating in the mechanism are taken from the Caster work [14].…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the energy values showed that all pathways were found to be strongly exothermic, and all the stationary points found lied well below the energy of the reactants [14]. From the TSs geometries, we have now conducted the IRC calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, expansion of a five-membered ring to a six-membered ring has been demonstrated through the reaction of pyrrole with the methylidyne radical (CH) to form pyridine 50 , and the reaction of cyclopentadiene with CH to form benzene (Figure 1c) 51,52 . CH in its ground state has been detected in combustion environments [53][54][55] , the interstellar medium 56,57 and under plasma conditions 58 .…”
Section: Introductionmentioning
confidence: 99%
“…CH in its ground state has been detected in combustion environments [53][54][55] , the interstellar medium 56,57 and under plasma conditions 58 . Reactions between CH and small unsaturated hydrocarbons and carbonyls can result in CH insertion to a π-bond through a cyclic intermediate (cycloaddition) followed by ring-opening 51,[59][60][61][62] . This reaction has a negligible activation barrier, resulting in fast reaction rates.…”
Section: Introductionmentioning
confidence: 99%